Pulling the strings unravelling the spatial and technical aspects in the design of a modern multi-use Puppet Arts Center - Arreglado, Artgiveson (College of Architecture, University of the Philippines Diliman, 2025)
The study aims to determine the spatial aspects and socio-cultural relevance of establishing a Puppet Arts Center in Metro Manila, informing the design of dedicated spaces for the development and promotion of puppet arts in the Philippines. This center will include facilities such as theaters, galleries, workshops and production areas, and spaces for exhibitions and performances, catering to both traditional theater puppet arts and shadow play. By establishing a centralized venue, the Puppet Arts Center aims to engage individuals, institutions, and the public, emphasizing the cultural significance of puppetry in Filipino heritage. Through this study, the author aims to contribute to the academic and professional discourse on the architecture of cultural facilities and its role in community engagement and cultural preservation.